The Influence of Picture Strip Story towards Students’ Speaking Skill - Khaulia Hanifa; Ilzamudin Ma’mur; Anita Anita (Scope : Journal of English Language Teaching, 2023)
This research is aimed to find out the influence of picture strip story towards student’s speaking skill at the second grade students of SMP Negeri 1 Cisoka Kab. Tangerang. The purposes of the research are: 1) to identify students’ speaking skill at the second grade student in SMP Negeri 1 Cisoka; 2) to define the appropriate technique to influence students’ speaking skill at SMP Negeri 1 Cisoka; and 3) to identify the effectiveness of picture strip story on students’ speaking skill at the second grade students in SMP Negeri 1 Cisoka. This research used a quantitative method with quasi experiment design, with 73 students as samples and divided into two classes, namely the control class and the experiment class. The results show the mean of posttest the experiment class is higher than control class 63, 3. Based on the statistical calculation the value of t_o (5, 77), and df (71) in significance 5% (t_table= 2, 38) and significance 1% (t_table = 1, 66). From comparing the t_o and t_table  the result is  t_o > t_table= 5, 77 > 1, 66 and to > t_table= 5, 77 > 2, 38. It means that  t_observation (t_o) is higher than  t_table (t_t), so Null Hypothesis (H_o) is rejected and Alternative Hypothesis (H_a) is accepted. It can be concluded that picture story can influence students’ speaking skills by improving several aspects including students’ fluency, vocabulary, pronunciation, grammar, and comprehension.